Virulence of Naegleria fowleri affected by axenic cultivation and passage in mice - John, D T; Howard, M J (Folia parasitologica, 1993)
The virulence of Naegleria fowleri decreases with prolonged axenic cultivation. The decline in virulence of highly virulent, mouse-passaged LEE strain amebae was monitored during 5 years of continuous axenic cultivation. The most rapid decrease in virulence occurred during the first 2 years. Virulence could be restored to original levels by 3 serial passages in mice. The composition of axenic media also affected the virulence of N. fowleri, with a more enriched medium appearing to restore some of the virulence of a weakly virulent strain.
Keywords: Virulence; Animals; gnotobiologické modely; virulence; sériové pasážování; mužské pohlaví; zvířata; Germ-Free Life; Male; Mice; Serial Passage; Naegleria fowleri; myši